Study of Anthropomentric and Morphometric Parameters in the Training of Athletes - Каратєєва, С.Ю.; Слободян, О.М.; Мосейчук, Юрій; Гауряк, Олена; Гой, О.Д. (Український журнал медицини, біології та спорту, 2021)
The purpose of the work was to study the patterns of development and formation of the structure of the skeletal, muscular, circulatory system under the influence of various physical activities in the dynamics, followed by the definition of correlations of the value of anthropometric and morphometric parameters in the training of athletes. Studying of the literature data, we can conclude that modern professional sports requires loads close to maximum, and sometimes even exceeding them, the establishment of these maximum permissible loads and the study of the patterns of their development is a very urgent task. The main problem in training athletes is adequate selection and sports affiliation. Solving the problems of selection involves the creation of a model of the athlete of this specialization, that is a certain set of characteristics that determine athletic performance. This requires anthropometric assessment, morphometric and biometric data to track physical and physiological parameters, information to assess performance and recovery in sports, modification of training regimes to prevent injuries, provide guidance on regulating the use of technologies used in professional sports, as well as to research and make recommendations for the proper collection, storage and exchange of health information. One of important problems of modern morphology is the study of changes that occur in the body under the influence of various factors. This problem has become especially important in connection with the development of sports. High sports performance, associated with a significant load on the athlete’s body, encourages scientists, doctors, coaches to search for physiological reserves of the body and search for optimal training regimes. From this point of view, the study of changes that occur in individual organs, systems and in the body as a whole, under the influence of physical activity of varying intensity and nature is relevant and of great practical importance. Conclusion. Modern professional sports require loads that are close to the maximum, and sometimes are such or exceed them. It is the establishment of these maximum allowable loads and study the patterns of their development which is a very promising area. This will allow timely selection of athletes for a particular sport, to carry out preventive and curative measures to improve their structural and functional condition.
Keywords: athletes, anthropometry, morphometry